Hyperkalemia-Related Renin Angiotensin-Aldosterone System Inhibitors: Mechanism, Clinical Significance, and Management - Akbar, Rizal Rahmanda (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Hyperkalemia refers to a medical condition in which potassium levels in the blood increase beyond normal values. This condition often occurs in patients suffering from chronic kidney disease (CKD) and heart failure, which can lead to serious complications and require special treatment from a cardiologist. Factors such as chronic kidney disease, heart failure, diabetes mellitus, and the use of drugs that inhibit the Renin-Angiotensin-Aldosterone (RAA) system are known to be a support that causes hyperkalemia. Using qualitative research methods, this approach focuses on semi-structured interviews with cardiologists, nephrologists, endocrinologists, and nurses who have experience in treating patients with hyperkalemia. Meanwhile, patients' perspectives will also be accommodated through group focus to understand their clinical impact and experience. The aim of this study was to investigate the mechanisms associated with angiotensin-aldosterone renin system (RAA) inhibitors related to hyperkalemia, as well as identify their clinical significance. In addition, this study aims to understand and analyze management strategies that can be applied in overcoming hyperkalemia associated with the use of RAA System inhibitors. Further objectives include providing in-depth insight into the impact of RAA System inhibition on potassium balance in the blood, evaluating the clinical significance of RAA-inhibitor-induced hyperkalemia conditions, and devising effective guidelines for hyperkalemia management in the context of the use of such drugs.